Religion and literacies in higher education: scoping the possibilities for faith-based meaning making - Smith, Paul Vincent (Critical Studies in Teaching and Learning, 2023)
Academic literacies pursues a transformative agenda, which involves ‘exploring alternative ways of meaning making in academia, not least by considering the resources that (student) writers bring to the academy as legitimate tools for meaning making’(Lillis andScott,2007: 13). How we select what the legitimate tools for meaning making are is assumed in these studies, but not established. Given the generally fraught status of religion in the academy, a perspicuous instance of this problem resides in the question of whether religious faith constitutes a ‘legitimate tool for meaning making’. We therefore need to think about how we establish what can and cannot be said to be legitimate tools, and whether this should be decided as a matter of normative principle, or whether it can be arrived at empirically. Further, we would need to consider how such questions are to be properly incorporated into learning and assessment. This article uses qualitative data from studies into religion and higher education to provide some initial thoughts on how these questions could be addressed. It carries out a scoping exercise that sheds light on the possibilities of the employment of religious identity in academic writing. It concludes that religious ideas and identities may on occasion be relevant without implying a threat to disciplinary rigour.